The Relationship Betweeen Knowlegde Of Pregnant Women Who Have Anemia And Complience With Consuming Fe Tablets At Rimenda’s Clinic Medan City - Wulandari, Berti; Wahyuni, Retno; Adethia, Kismiasih (Mitra Husada Health Internasional Conference (MIHHICo), 2023)
Background: Almost half or as many as 48.9% of pregnant women in Indonesia suffer from anemia or lack of blood (Riskesdas, 2014). Based on the results of data from the Basic Health Research (Riskesdes) in 2018, the proportion of pregnant women who experienced anemia increased, compared to the results in 2013 which was 37.1%. From the data in 2018, the highest number of pregnant women who experienced anemia was at the age of 15-24 years at 84.6%, aged 25-34 years at 33.7%, 35-44 years old at 33.6%, and age 45 -54 by 24%. In addition, for women of childbearing age who were not pregnant, 20.8% in 2013 decreased to 14.5% in 2018. The prevalence of anemia and the risk of chronic energy deficiency in women in the suburbs greatly affects the condition of their children when they rise (Ministry of Health, 2014). Methods: This study used non-probability sampling with sampling using total sampling. Data collection Using interview techniques and checklists. The data analysis used was univariate analysis with presentation and bivariate analysis with Chi-Square test. Conclusion: The conclusion in this study obtained significant results between the knowledge of pregnant women with aneemia and compliance with consuming Fe tablets at the Rimenda Br. Tarigan Clinic, Medan Denai District in 2019.